The Effect of Project Based Learning (PJBL) Model Based on Marharoan Bolon in Science Subjects on Students' Learning Outcomes in Grade V UPTD SD Negeri 122379 Pematangsiantar - Sirait, Khorint Meilani; Thesalonika, Emelda; Sijabat, Desi (MSJ : Majority Science Journal, 2025)
This study aims to determine the effect of the Project Based Learning (PjBL) model based on Marharoan Bolon in the Science Subject on the Learning Outcomes of Class V Students of UPTD SD Negeri 122379 Pematangsiantar. In this study, the research design used ispre-experimental designwith typeOne-Group Pretest-Posttest Design. Population is the entire research sample. In this study, the sample was 20 students of grade V of UPTD SD Negeri 122379 Jln. Sentosa, Pematangsiantar City. The instrument trials were question validity tests, reliability tests, difficulty level tests, and discrimination power tests. Data collection techniques in this study used tests and documentation, with data analysis techniques, namely normality tests, t-tests, and N-Gain tests. Based on the learning outcomes obtained during the study of the use of the Marharoan Bolon-based Project Based Learning Model in the subject of Social Sciences on the learning outcomes of class V students of UPTD SD Negeri 122379 Pematangsiantar, tcount = 22.08> ttable = 1.72 and significant = 0.00 <0.05. From these results it can be seen that Ha is accepted which means that there is an influence of the use of the Marharoan Bolon-based Project Based Learning model in the subject of Social Sciences on the learning outcomes of class V students of UPTD SD Negeri 122379 Pematangsiantar.